Lung Resection for Trauma: A Propensity Score Adjusted Analysis Comparing Wedge Resection, Lobectomy, and Pneumonectomy. Issue 3 (March 2020) - Aiolfi, Alberto; Inaba, Kenji; Martin, Matthew; Matsushima, Kazuhide; Bonitta, Gianluca; Bona, Davide; Demetriades, Demetrios
The resection of lung parenchyma for thoracic trauma is uncommon. Different surgical procedures with a wide range of complexities have been described depending on the severity of trauma and the presence of associated injuries. The aim of this study was to analyze outcomes of wedge resection, lobectomy, and pneumonectomy. Data for this study were obtained from an eight-year retrospective National Trauma Data Bank study (2007–2015). Adult patients who sustained severe chest trauma (Abbreviated Injury Scale > 3) that required any type of lung resection were included. Propensity score (PS) analysis was adopted. Overall, 3107 patients were included. Wedge resection was performed in 54.3 per cent, lobectomy in 38.2 per cent, and pneumonectomy in 7.5 per cent of patients. Longer in-hospital length of stay ( P = 0.01), ICU length of stay ( P = 0.002), and mechanical ventilation days ( P = 0.038) were found in case of major resections. The overall morbidity and mortality were 32 per cent and 27.5 per cent, respectively. A stepwise increase in mortality occurred when comparing wedge (20.3%), lobectomy (30.8%), and pneumonectomy (63.4%) ( P < 0.001). After PS analysis, lobectomy and pneumonectomy were associated with higher mortality compared with wedge resection (odds ratio [OR] 1.42; 95% confidence interval 1.26–1.71 and OR 4.16; 95% confidence interval 2.84–6.07, respectively). Similarly, after PS analysis, lobectomy and pneumonectomy were associated with higher overall complications compared with wedge resection (OR 1.21 and OR 1.56, respectively). Comparable results were found in the subgroup analysis of patients with isolated lung injury. After PS matching, lobectomy and pneumonectomy were associated with significantly higher morbidity and mortality compared with nonanatomical wedge resection.